2011
DOI: 10.1007/s11010-011-0732-6
|View full text |Cite
|
Sign up to set email alerts
|

The influence of training status on oxidative stress in young male handball players

Abstract: Although exercise-induced oxidative stress receives considerable scientific attention, there is still little information available regarding exercise-induced adaptations of the antioxidant defence system in adolescent and child athletes. The aim of our study was to establish the effects of long-term exercise training on the redox state of adolescents, and to find correlations between elements of redox homeostasis and aerobic power. Thirty-three handball players and 14 non-athletes, 16-19-years old, were subjec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
31
1
8

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 51 publications
3
31
1
8
Order By: Relevance
“…However, because it has been shown that endogenous oestrogen may have a protective role in exercise-induced oxidative stress among female handball players [38] and female non-ath- exercise load and consequently longer duration of the exercise test. Positive correlation between VO 2max and H 2 O 2 levels was previously established [3].…”
Section: Statisticsmentioning
confidence: 64%
See 3 more Smart Citations
“…However, because it has been shown that endogenous oestrogen may have a protective role in exercise-induced oxidative stress among female handball players [38] and female non-ath- exercise load and consequently longer duration of the exercise test. Positive correlation between VO 2max and H 2 O 2 levels was previously established [3].…”
Section: Statisticsmentioning
confidence: 64%
“…Detection was performed at 470 nm. The activities of SOD and CAT in RBCs are presented in units per gram of haemoglobin x10 3 (U/g Hbx10…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Что касается отсутствия достоверного прироста в кле-точных мембранах содержания природного антиок-сиданта восстановленного глутатиона в основной подгруппе 1А у легкоатлетов, то, следует отме-тить, что определяющим параметром влияния на ПАР является преимущественное снижение содер-жание малонового диальдегида, поскольку иссле-дуемый препарат выступает как антиоксидант, т.е. субстанция, в первую очередь, ограничивающая выраженность прооксидантных реакций [25,31,32] и, следовательно, повышающая толерантность к физической работе циклического характера [38] Наблюдаемое у представителей тяжелой атлетики отсутствие достоверных изменений в динамике исследования (между данными в Т начало и Т окончание ) изучаемых параметров ПАР в контрольной под-группе лишь подтверждает существенное ограни-чивающее действие препарата на основе L-аргинина на баланс прооксидантных и антиокси-дантных факторов при преимущественно лактат-ном гликолитическом типе энергообеспечения мышечной деятельности [45,51]. Можно также говорить о нормализации ПАР в мембранах эрит-роцитов как о факторе, нормализующем структур-но-функциональное состояние этих клеток и опо-средованно улучшающем скорость переноса ки-слорода [4,6,7] при соответствующем снижении вязкости крови, что в целом позитивно влияет на кислородтранспортную функцию крови, являю-щуюся одним из важнейших факторов реализации аэробных возможностей спортсмена в циклических видах спорта [12,14,16,17].…”
unclassified